2017
DOI: 10.1111/jan.13256
|View full text |Cite
|
Sign up to set email alerts
|

Self‐administered health literacy instruments for people with diabetes: systematic review of measurement properties

Abstract: With the current evidence, the Health Literacy Scale may be the most appropriate instrument for patients with diabetes in practice and research. However, the structural validity of this scale needs to be further established, particularly in other language versions. It is also recommended to use the Diabetes Numeracy Test-15 along with the Health Literacy Scale to complement the lack of numeracy measures in the Health Literacy Scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…Lee et al. () conducted a systematic review of the psychometric properties of diabetes‐specific health literacy instruments and found that based on the current evidence, the HLS is the most appropriate instrument for measuring diabetes‐specific health literacy. However, since the HLS does not include a numeracy component, they suggested using a scale with a numeracy measure such as the Diabetes Numeracy Test‐15 (Huizinga et al., ), which should be addressed in a future study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al. () conducted a systematic review of the psychometric properties of diabetes‐specific health literacy instruments and found that based on the current evidence, the HLS is the most appropriate instrument for measuring diabetes‐specific health literacy. However, since the HLS does not include a numeracy component, they suggested using a scale with a numeracy measure such as the Diabetes Numeracy Test‐15 (Huizinga et al., ), which should be addressed in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…The HLS score was computed as the average for all items, with a higher score indicating better health literacy. This study used the Korean version of the HLS that exhibits internal consistency reliability, factorial construct validity and known‐groups validity in Korean people with diabetes (Lee et al., ). Cronbach's alpha for the scale used in the present study was 0.92.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is the variety of definitions and measurements of health literacy. 12,13 In clinical settings, health literacy has been traditionally assessed with word recognition tests like the Rapid Estimate of Adult Literacy in Medicine (REALM 12 ) or combined health literacy and numeracy tests like the Short Test of Functional Health Literacy (S-TOFHLA 13 ). These tests measure patients' performance, i.e., basic comprehension, reading, and numeracy skills.…”
Section: Introductionmentioning
confidence: 99%
“…The third issue is related to the lack of psychometric properties. In accordance with a systematic review of measurement properties [16], three objective instruments have been developed for assessing health numeracy for patients with diabetes: diabetes numeracy test-43 (DNT-43) [4], its short-form DNT-15 [17], and brief numeracy [18]. As the results of the systematic review [16], these instruments had no, unclear, or only limited evidence for most of their psychometric properties, implying the need for a new objective instrument measuring health numeracy for patients with diabetes.…”
Section: Introductionmentioning
confidence: 75%